2022
DOI: 10.1038/s41598-022-06075-0
|View full text |Cite
|
Sign up to set email alerts
|

Network flow and flood routing model for water resources optimization

Abstract: Real-time management of hydraulic systems composed of multi-reservoir involves conflicting objectives. Its representation requires complex variables to consider all the systems dynamics. Interfacing simulation model with optimization algorithm permits to integrate flow routing into reservoir operation decisions and consists in solving separately hydraulic and operational constraints, but it requires that the water resource management model is based on an evolutionary algorithm. Considering channel routing in o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…On the other hand, these results confirm the findings by Tahiri et al (2022) and Moradi et al (2023), since, as demonstrated in the present investigation, the Muskingum method is an efficient technique in terms of flow generation from historical records available from hydrometric stations, especially in the data processing time, the application equations and flood routing estimation parameters.…”
Section: Resultssupporting
confidence: 93%
“…On the other hand, these results confirm the findings by Tahiri et al (2022) and Moradi et al (2023), since, as demonstrated in the present investigation, the Muskingum method is an efficient technique in terms of flow generation from historical records available from hydrometric stations, especially in the data processing time, the application equations and flood routing estimation parameters.…”
Section: Resultssupporting
confidence: 93%
“…Measures such as improving irrigation techniques, promoting water-saving devices, and optimizing water supply systems have been implemented to enhance water resource utilization efficiency (Castellini et al, 2022). Additionally, water resource scheduling research has been conducted using mathematical models and optimization algorithms to achieve rational allocation and distribution of water resources, improving the level of supplydemand matching (Tahiri et al, 2022).…”
Section: Research Progress Of Water Resources Security Optimizationmentioning
confidence: 99%